Near-fatal asthma as clinical manifestation in onset diabetic patient: Case report: Asma casi fatal como manifestación clínica en paciente diabética debut: Reporte de caso - Chávez Paredes, César A. (2022)
Near-fatal asthma (NFA) is defined as the most severe form of asthma characterized by a refractory asthma attack with an arterial carbon dioxide tension (PaCO2) greater than 45 mmHg and altered consciousness, requiring mechanical ventilation. We reported the case of 40-year-old female patient, obese and asthmatic with irregular treatment who presented dyspnea accompanied by severe oppressive chest pain and loss of consciousness, with generalized cyanosis and severe shortness of breath, for which she underwent emergency endotracheal intubation and mechanical ventilation. Laboratory tests show decompensated respiratory acidosis, glycemia of 258 mg / dl and HbA1C of 7.94%; her diagnosing diabetes mellitus. Asthmatic patients with type 2 diabetes mellitus who have irregular treatment for both diseases are at increased risk of manifesting near-fatal asthma.